Analisis Pengaruh Debt to Asset Ratio, Return on Asset dan Current Ratio terhadap Return Saham - Pungki Mega Sahara; Gendro Wiyono; Pristin Prima Sari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the effect of Debt to Asset Ratio (DAR), Return On Assets (ROA) and Curret Ratio (CR) on stock returns. This research uses quantitative research, the sampling technique is purposive sampling method, namely because it can choose certain targets that can provide information based on predetermined criteria. So, in this study, the population taken was all Manufacturing companies in the industrial sector for the 2018-2021 period which were listed on the Indonesia Stock Exchange (IDX) as many as 32 companies. The method of collecting data is secondary data, which is the financial statements of companies that make stock returns. The amount of data used is 128 samples. From what was done, the results of the study showed that the Debt to Asset Ratio (DAR), Return On Assets (ROA) and Current Ratio (CR) did not affect stock returns as evidenced by the significant value of each variable greater than 0.05. Keywords: Debt to Asset Ratio (DAR), Return On Assets (ROA), Current Ratio (CR), and Stock Return.